Young People and Pancasila: The Current Challenges - Anggraeni, Fitri Inda (Journal of Creativity Student, 2019)
Indonesia has the ideology and basis of the state, namely Pancasila, Pancasila is the basis of the state or often also referred to as the basis of state philosophy, state ideology (staatside). In this case, Pancasila is used as the basis for regulating state government. In other words, Pancasila is used as the basis for regulating all state administration. Pancasila mixes five precepts, namely divinity in the one and only God, just and compassionate humanity, the unity of Indonesia, democracy led by wisdom in representative deliberation, and the last one is social justice for all Indonesian people. These five Pancasila must be interpreted and implemented in their entirety by Indonesian citizens. Meanwhile, in this era of globalization, many people ignore Pancasila. Pancasila can be accepted by all groups and groups of people in Indonesia. However, following the development of the millennial generation, many young people forget Pancasila and do not implement it in their daily lives. There are many challenges of Pancasila in this millennial generation itself. In the growth of the millennial generation, there are many challenges in instilling and implementing Pancasila in their lives. There are many young people who get westernized currents that are different from the culture in Indonesia and different from Pancasila. This is our effort to make Pancasila a reality in the lives of these millennial generations. One of them is Pancasila education up to the level of lectures. The millennial generation, the term was coined by two American historians, namely William Strauss and Neil Howe. The millennial generation or generation Y is also known as the me generation or echo boomers. Generation Y is classified by year of birth, namely for those born in 1980-1990 or early 2000 and so on. Most of the millennial generation in their lives use technology such as SMS, instant massage, social media such as Instagram, YouTube, and enthusiasts with online games. While the challenge of Pancasila in the current era, namely the millennials, is very felt, with globalization where all information can be entered and obtained easily because technology makes foreign cultures enter, where the ideology is not in accordance with the culture and ideology of the Indonesian nation.